2014
DOI: 10.1021/cm5006482
|View full text |Cite
|
Sign up to set email alerts
|

Partial Ion-Exchange of Nickel-Sulfide-Derived Electrodes for High Performance Supercapacitors

Abstract: A novel method to adjust the composition of a material while maintaining its morphology was described in this study. Nickel sulfide, the material investigated in this work, was found to be useful as a high surface area electrode material for supercapacitor applications. First, a nest-like Ni 3 S 2 @NiS composite electrode with 1D nanorod as structural unit was synthesized by simultaneously using Ni foam as template and Ni as a source through a one-step in situ growth method. Co and Se ions, which respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
161
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(174 citation statements)
references
References 48 publications
10
161
3
Order By: Relevance
“…The diffraction peaks at 2θ = 21.8, 31.1, 37.8, 38.3, 49.9, 50.2, 54.6 and 55.1°, respectively, correspond to the Figure S1) is also observed in the X-ray diffraction pattern, which was also frequently observed when Ni foam was used as a template and/or Ni source to prepare Ni 3 S 2 using a one-step in situ growth method. 27,29 All samples prepared at different temperatures displayed the same structure, as also confirmed by Raman spectroscopy (Supplementary Figure S2).…”
Section: Resultssupporting
confidence: 65%
“…The diffraction peaks at 2θ = 21.8, 31.1, 37.8, 38.3, 49.9, 50.2, 54.6 and 55.1°, respectively, correspond to the Figure S1) is also observed in the X-ray diffraction pattern, which was also frequently observed when Ni foam was used as a template and/or Ni source to prepare Ni 3 S 2 using a one-step in situ growth method. 27,29 All samples prepared at different temperatures displayed the same structure, as also confirmed by Raman spectroscopy (Supplementary Figure S2).…”
Section: Resultssupporting
confidence: 65%
“…Besides, it is noted that the ion-exchange reaction could adjust the composition, structure and properties, taking a great effect on the purity and morphology of the NiCo2S4 [15,16] and it seems hard to obtain pure spinel NiCo2S4 by directly reacting Ni 2+ and Co 2+ with S 2-. Some sulphides such as Na2S [8,14,[17][18][19], thiourea [20,21] and thioacetamide [9,14] have been employed to prepared NiCo2S4 recently, and excellent electrochemical performance was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…42-1467), indicating that the introduction of nickel ions does not change the spinel structure of the samples [21,31]. According to the results above, it can be concluded that partial Co ions of the spinel Co 3 O 4 are replaced by Ni ions during the electrochemical process while maintaining its crystal structure and morphology, which lead to the formation of the hybrid spinel Co 3 O 4 / NiCo 2 O 4 nanocomposites [22,23,27,28].…”
Section: Results and Disscussionmentioning
confidence: 98%
“…For example, Jiao et al [25] reported the partial substitution of Ni 2+ in a Ni-MOF by active Co 2+ via a hydrothermal method and the obtained CoNi-MOF exhibited a high specific capacity of 236.1 mA h g -1 at a current density of 1 A g -1 ; Zhang et al [26] obtained core@shell Co 3 O 4 @NiCo 2 O 4 nanowire arrays on Ni foam via a hydrothermal and co-electrodeposition method, exhibiting a high areal capacitance of 2.04 F cm -2 at a current density of 5 mA cm -2 . Wu et al [22] [27,28]. Benefiting from the synergistic effect, the Co 3 O 4 /NiCo 2 O 4 composite electrode delivers a high areal capacity of 3.2 F cm -2 at a current density of 5 mA cm -2 and excellent rate capability as well as long cycle stability.…”
Section: Introductionmentioning
confidence: 99%